The Origin of Electrochemical Actuation of MnO2/Ni Bilayer Film Derived by Redox Pseudocapacitive Process. (9th January 2019) - Liu, Lingyang; Su, Lijun; Lu, Yulan; Zhang, Qingnuan; Zhang, Li; Lei, Shulai; Shi, Siqi; Levi, Mikhael D.; Yan, Xingbin
Abstract: Pseudocapacitance‐induced electrochemical actuators (EC‐actuators) have attracted great attention in robots and artificial intelligence technologies. Despite major efforts to design such EC‐actuators, a molecular‐level understanding of the deformation mechanism is still lacking. Here, a reversible deformation of a freestanding MnO2 /Ni bilayer film is demonstrated and in situ electrochemical atomic force microscopy, in situ Raman spectroscopy, and density functional theory simulation are used to study the origin of the deformation. The results show that the electrochemical actuation of the MnO2 /Ni film is highly related with the redox pseudocapacitive behavior of MnO2 layer. Valence state variation of Mn element, shortening and lengthening of MnO bond, and insertion and extraction of Na + ions, which all result from the redox pseudocapacitance of MnO2 during charging and discharging, eventually lead to the reversible contraction and expansion of MnO2 morphology. Such action counters with the nonactive Ni layer, finally inducing the reversible deformation of the MnO2 /Ni bilayer film. It is believed that the study can provide useful guidance to design better EC‐actuators in the future. Abstract : A redox pseudocapacitive MnO2 /Ni bilayer electrochemical actuator is demonstrated and the deformation mechanism is investigated by several in situ measurements. Pseudocapacitance causes a valence change in Mn, shortening/lengthening of the MnO bond along with the insertion/extraction of Na + ions, thus leading to the volume variation of MnO2, while countering with the non‐active Ni layer, finally resulting in the actuation.